The effects of mid-altitude on endocrine profil - Coksevim, B.; Narin, F.; Yaba, G. (Biology of Sport, 2006)
Many of the physiologic changes that occur during acute and prolonged altitude exposure may actually negate adaptations that possibly improve physiologic performance upon return to sea level. Fourteen volunteer male students (male scouts) who inhabit at 1050 m were enrolled into the study to research; how mid-altitude affects some endocrine parameters. The basic evaluation was done before the camping at 3200 m, and the endocrine evaluation was repeated 10 days after, at the end of the camping.